Aspek Moral Dalam Novel Hafalan Shalat DelisaKarya Tere Liye: Tinjauan Sosiologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra di SMA - Nugroho, Dimas Permady Anjar; , Drs. Zainal Arifin, M.Hum (2017)
The study aims to describe (1) the sociohistoric background of Hafalan Shalat Delisa's author (2) the structure that de-velop in Hafalan Shalat Delisa novel (3) the moral aspect in Hafalan Shalat Delisa novel, and (4) the implementation of the result of the novel as literary materials in high school. The nature of this research in qualitative descriptive research. The object of this research is to moral aspects of Hafalan Shalat Delisa novel. The data of this research is a sentences or paragraph that contains the structure and moral aspects. The primary data sources in this research is Hafalan Shalat Delisa novel author by Tere Liye. The secondary data sources in this research is reference book or articles. Data collection technique used in this research is the literature, observe, record, and interview. The validity technique of the data used the triangular resources and triangular theory technique. Data analysis technique used is the technique dialectic. The result of the analysis can be summed up as follows. (1) based on socio-historic of Tere Liye, the author of Hafalan Shalat Delisa novel. (2) structural analysis the theme of the novel is un easy to give up, patient, and determined. The flow of the story is advanced flow (progressive). The main character is Delisa and the supporting character is Ummi Salamah, Kak Fatimah, Kak Aisyah, Kak Zahra, Abi Usman, Koh Acan, Ustadz Rahman,Ibu Guru Nur, Sersan Ahmed, Prajurit Smith/Salam, Suster Shopi, Tiur, Umam, and Kak Ubai. The setting located in Lhok Nga, Ship, and Hospital, the time setting occured between 2004 to 2005, the social background og Hafalan Shalat Delisa is about habit, tradition, and religious belief. (3) the moral aspects in the Hafalan Shalat Delisa novel by Tere Liye are such as issues of honesty, authentic, responsibility, be autonomous,and realistic and critical. (4) the results of this research are implemented as literary materials in senior high school based on the SK 7 i.e. understand the various saga, Indonesian novel or translation and KD 7.2 i.e. analyze the intrinsic and extrinsic elements of Indonesian novel or translations.